Spiritual Crisis: The Consequences of Forgetting Allah in the Qur’an - Randy Febriananta Primayudha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Forgetfulness is one of the inherent traits of humans. It can occur because information stored in the brain has been replaced or obscured by new information. Forgetting is initially beyond human control because it is located in a part of the brain called the hippocampus, which functions to regulate memory or process information received by human senses. However, it is different from